The university role in new teacher learning - why it matters: Teach First trainee perspectives (UCL Press, 2023)
An emphasis on school-led initial teacher training (ITT) in England has marginalised the university role and led to instrumental models of new teacher learning. Rather than commit to continued university involvement in new teacher learning like the rest of the UK, England appears to be following in the footsteps of the USA, where new graduate schools of education (nGSEs) train teachers without university input. School leaders and academics have sought to articulate the value of the university role in initial teacher education (ITE), but there is little understanding of trainee teacher perspectives. This article presents findings from in-depth qualitative research with Teach First trainees at IOE, UCL's Faculty of Education and Society (University College London, UK). Trainee perspectives on the university role in their learning are explored, before the implications for the future of ITE and ITT are considered. Findings indicate a need to reposition the university as an inspirational learning environment for teachers from the beginning of, and throughout, their careers, enabling sustained critical and creative thinking away from the school context, so that, as one trainee articulates, teachers do not 'stagnate because there is no distraction from the day job', but continue to develop and maintain their commitment to the profession.